Identification of F11 fimbriae on chicken Escherichia coli strains. - van den Bosch, J F (1993)
Fimbriae were purified from Escherichia coli strains isolated from chickens with septicemia or colibacillosis. When grown on solid media, these strains expressed fimbriae with an apparent subunit molecular mass of 18 kDa. Morphological, biochemical, serological, functional, and molecular characterization revealed that these 18-kDa fimbriae are identical to F11 fimbriae, which were previously found to be involved in the pathogenesis of human urinary tract infection. Screening of a large strain collection showed that 78% of chicken E. coli strains expressed F11 fimbriae, whereas this percentage increased to 96% when the only strains taken into account were those with the serotypes most commonly encountered in avian colibacillosis (O1:K1, O2:K1, O35, and O78:K80). The prevalence of F11 fimbrial expression appeared to be independent of the country of isolation of the strains, except for the United States, where the prevalence seemed higher. Expression of F11 fimbriae by chicken E. coli strains could not be correlated with adherence to chicken tracheal or pharyngeal cells.